Observation of the photovoltaic effect in a van der Waals heterostructure. Issue 12 (8th March 2023) - Zhang, Shaochun; Maruyama, Mina; Okada, Susumu; Xue, Mengsong; Watanabe, Kenji; Taniguchi, Takashi; Hashimoto, Kazuki; Miyata, Yasumitsu; Canton-Vitoria, Ruben; Kitaura, Ryo
Abstract : A van der Waals heterostructure composed of WS2 /MoS2 showing a photovoltaic effect with an excitation wavelength of 633 nm. Abstract : van der Waals (vdW) heterostructures, which can be assembled with various two-dimensional materials, provide a versatile platform for exploring emergent phenomena. Here, we report an observation of the photovoltaic effect in a WS2 /MoS2 vdW heterostructure. Light excitation of WS2 /MoS2 at a wavelength of 633 nm yields a photocurrent without applying bias voltages, and the excitation power dependence of the photocurrent shows characteristic crossover from a linear to square root dependence. Photocurrent mapping has clearly shown that the observed photovoltaic effect arises from the WS2 /MoS2 region, not from Schottky junctions at electrode contacts. Kelvin probe microscopy observations show no slope in the electrostatic potential, excluding the possibility that the photocurrent originates from an unintentionally formed built-in potential.